Analysing the Mobile Telecommunications Market in a Developing Country : A Socio-Technical Perspective on Pakistan /: A Socio-Technical Perspective on Pakistan. (2009) - (Senior lecturer in information systems), Gao, Ping; Rafiq, Adnan
No abstract available